Double D–π–A Dye Linked by 2, 2′‐Bipyridine Dicarboxylic Acid: Influence of para‐ and meta‐Substituted Carboxyl Anchoring Group. Issue 5 (5th February 2015) - Ganesan, Paramaguru; Chandiran, Aravind Kumar; Gao, Peng; Rajalingam, Renganathan; Grätzel, Michael; Nazeeruddin, Mohammad Khaja
Abstract: Starting from 2, 2′‐bipyridine dicarboxylic acid, two new (D –π–A)2 sensitizers, including m ‐DA with the carboxyl anchoring group substituted meta to the donor‐bridge moiety and p ‐DA with a para ‐substituted anchoring group, were synthesized in order to evaluate the impact of the position of the anchoring group on the optical, electrochemical, and photovoltaic properties of dye‐sensitized solar cells. p ‐DA exhibits red‐shifted absorption behavior compared to m ‐DA, owing to the more efficiently extended π‐conjugation with para substitution. Both m ‐DA and p ‐DA are adsorbed on the mesoporous TiO2 surface by using both of their carboxylic acid groups in a bianchoring mode, which is confirmed through attenuated total reflectance FTIR analysis. Red‐shifted absorption of p ‐DA assists the achievement of a red‐shifted incident photon‐to‐electron conversion efficiency and a higher short‐circuit current density than m ‐DA. The photogenerated electron lifetime in TiO2 is also found to be higher for para substituted p ‐DA than the meta ‐substituted m ‐DA, which results in a higher open‐circuit voltage. All of the results suggest that dicarboxyl‐2, 2′‐bipyridine can be used as an acceptor for metal‐free organic sensitizers. However, the anchoring segments should be adjusted to the favorable position of the corresponding donor‐bridge moieties for better conjugation. Abstract : On the bench: Two new (D –π–A)2 organic sensitizers ( m ‐DA, p ‐DA) employing a 2, 2′‐bipyridine dicarboxylic acid unit as an acceptor and anchoring group are designed. The m ‐DA has the anchoring part substituted meta to the donor moiety and p ‐DA has a para ‐substituted anchoring moiety. Overall, para ‐substituted p ‐DA exhibits better photovoltaic performance than meta ‐substituted m ‐DA.